Potential Utilization Rate of Anchovy in Dodinga Bay Waters with Scheafer and Fox Models (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research was conducted from November 2023 to January 2024 in the waters of Dodinga Bay with the aim of assessing the potential of anchovy using the Schefer and Fox methods. The method used is the experimental fishing method where researchers will directly participate in fishing activities during 40 fishing trips and carry out the data collection process in the form of fishing position, water temperature and anchovy length as the main data in the study. Based on the results of research by analyzing MSY based on the Fox model and Scheafer Model, it can be concluded that the R2 value of the Scheafer model is 0.7583 which is close to 1 so that the Scheafer model is the best model for calculating MSY of skipjack in Ternate Island waters with an MSY value or sustainable potential of 6,976.3 kg / year with a maximum effort of 192 trips. Furthermore, the level of skipjack utilization in Ternate Island waters during 2017-2022 is still low or less than 20%.
Keywords: Anchovy; Teluk Dodinga; MSY; Scheafer